Achieving Better Integration in Trauma Care Delivery in India: Insights from a Patient Survey. (September 2018) - Prætorius, Thim; Chaudhuri, Atanu; Venkataramanaiah, S.; Hasle, Peter; Singh, Ajai
Interdependencies among healthcare providers result in complex healthcare supply chains with fragmented healthcare processes characterized by coordination failure and incentive misalignment. In developing countries where resources are scarce such coordination failures can have a severe impact on patient health. However, limited knowledge exists about how coordination takes place across and within the different healthcare service providers and how this influences hospital transfer time and length of stay. This article research this gap by studying trauma care delivery in India using a patient survey ( n = 104). The Indian healthcare system is insightful because India has to provide low-cost care to large populations living in geographically big areas and the healthcare infrastructure struggles to meet increasing demands. The findings suggest mechanisms to better integrate the processes from the accident site to the hospital which include setting up referral processes, 24-hour ambulance services, using third-party coordinators and process improvement within the hospital following lean principles.